Effect of different organic amino cations on SAPO-34 for PES/SAPO-34 mixed matrix membranes toward CO2/CH4 separation - Ahmad, N.N.R. (John Wiley and Sons Inc., 2016)
Mixed matrix membranes (MMMs) embedded with functionalized SAPO-34 were successfully synthesized and characterized. Two different types of organic amino cation, namely ethylenediamine (EDA) and hexylamine (HA), were used to functionalize SAPO-34 particles prior to MMM synthesis. In this work, the effects of different functionalizing agents on the membrane morphology, pore size, and CO2/CH4 gas separation properties were investigated. Surface modification of SAPO-34 was confirmed via X-ray photoemission spectroscopy (XPS) where the presence of nitrogen atom was observed for the samples functionalized with amino cations. The dispersion of EDA-functionalized SAPO-34 particles was found to have better polymer/filler interface morphology as shown by field emission scanning electron microscopy (FESEM) analysis. The gas separation performance revealed that PES containing EDA-functionalized SAPO-34 exhibited better CO2/CH4 separation performance as compared to the MMMs containing HA-functionalized SAPO-34. Â© 2016 Wiley Periodicals, Inc.